Identification of Ferroptosis-Related Genes Associated With Cryptorchidism via Bioinformatics and Experimental Verification - Tian Du; Yifeng Ge; Zheng Zhou; Jun Jing; Yuming Feng; Hualong Ding; Jinzhao Ma; Bing Yao (Genetics Research)
Conclusion: Our study identified two ferroptosis-related genes, BRDT and PARP11 might play a role in the pathogenesis of spermatogenesis dysfunction in patients with cryptorchidism, which provided a novel perspective for the prevention and treatment of spermatogenesis dysfunction in patients with cryptorchidism in clinical practice.